2005
DOI: 10.7863/jum.2005.24.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Malignancy in Incidentally Discovered Thyroid Nodules Evaluated With Sonography and Fine-Needle Aspiration

Abstract: This study identified an unexpectedly high rate of malignancy in incidentally discovered thyroid nodules, suggesting that incidentally discovered thyroid nodules should be evaluated with follow-up thyroid sonography and FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 23 publications
0
48
1
1
Order By: Relevance
“…26,27 Thyroid nodules incidentally detected by ultrasound performed for carotid or parathyroid disease have a risk of malignancy of approximately 10%. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] Such nodules should undergo dedicated thyroid sonographic evaluation. Lesions with a maximum diameter Ͼ1.0 cm to 1.5 cm should undergo FNA, unless they are simple cysts or septated cysts with no solid elements.…”
Section: Indications For Performing An Fna Of a Thyroid Nodulementioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Thyroid nodules incidentally detected by ultrasound performed for carotid or parathyroid disease have a risk of malignancy of approximately 10%. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] Such nodules should undergo dedicated thyroid sonographic evaluation. Lesions with a maximum diameter Ͼ1.0 cm to 1.5 cm should undergo FNA, unless they are simple cysts or septated cysts with no solid elements.…”
Section: Indications For Performing An Fna Of a Thyroid Nodulementioning
confidence: 99%
“…Because recent guidelines recommend that all pa-tients with palpable nodules undergo ultrasound examination, 6,8,34,38 an increasing number of biopsies are now being performed with ultrasound guidance. Published data indicate that ultrasound evaluation and ultrasound guidance reduce the rate of nondiagnostic specimens and false-negative aspirates.…”
Section: Indications For Performing An Fna Of a Thyroid Nodulementioning
confidence: 99%
“…5 In our study risk of malignancy is 22.2%. One patient underwent right hemithyroidectomy and the other patient refused to undergo surgery.…”
Section: Figure 5: Sex-wise Distributionmentioning
confidence: 45%
“…Twothirds of cancers found are localized to the dominant nodule with the remaining cancers localized to the nondominant nodule. Liebeskind et al found that thyroid nodules discovered incidentally by ultrasound had a significantly higher risk of malignancy than those that were nonincidental (17% vs. 3%; p=0.20) [4].…”
Section: Allmentioning
confidence: 99%